2016
DOI: 10.1007/s00500-016-2240-9
|View full text |Cite
|
Sign up to set email alerts
|

A modified ant colony optimization algorithm for multi-objective assembly line balancing

Abstract: In this paper, a novel ant colony optimization algorithm called modified ant colony optimization algorithm (MACO) is proposed for multi-objective single-model assembly line balancing problem (SALBP). The proposed MACO presents a novel heuristic information combined with subsequent task number and deviation time that can guide ants to find better solutions for SALBP. The proposed MACO also adopts three assignment methods (i.e., forward, backward and local rebalancing assignment methods) and stratified sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
(25 reference statements)
0
17
0
1
Order By: Relevance
“…Kilbridge and Wester [16] found that task times usually follow a unimodal or bimodal distribution. Following Morrison et al [13], three kinds of task times are generated: (1) peak at the bottom: tasks times are drawn from a normal distribution with the mean centered around small times; (2) peak in the middle: task times are drawn from a normal distribution with a mean of C/2; (3) bimodal: task times are drawn from a combination of two normal distribution with means centered around small and large times. Task times are rounded to the next integer and possible rounding effects are compensated for by setting the default cycle time to 1000 to allow flexible time structures [14].…”
Section: Icmie 102-7mentioning
confidence: 99%
See 3 more Smart Citations
“…Kilbridge and Wester [16] found that task times usually follow a unimodal or bimodal distribution. Following Morrison et al [13], three kinds of task times are generated: (1) peak at the bottom: tasks times are drawn from a normal distribution with the mean centered around small times; (2) peak in the middle: task times are drawn from a normal distribution with a mean of C/2; (3) bimodal: task times are drawn from a combination of two normal distribution with means centered around small and large times. Task times are rounded to the next integer and possible rounding effects are compensated for by setting the default cycle time to 1000 to allow flexible time structures [14].…”
Section: Icmie 102-7mentioning
confidence: 99%
“…An assembly line is a continuous production line consisting of materials and workstations combined with conveyor belts, linking men and machines closely and efficiently [1]. Assembly lines are flow-oriented systems that are indispensable for both the production of high quantity standardized products and low volume production of customized products [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic version of the assembly line balancing problem is simple assembly line balancing problem (ALBP) with workstation minimization criterion, referred to as type I ALBP (Boysen et al 2007;Chica et al 2015). Another widely researched objective function is minimizing cycle time, leading to a more complex ALBP referred to as type II ALBP (Zhong and Ai 2017). Type I ALBP has been criticized for lacking real-life application and being too theoretical since the environment in real industry is much more complex.…”
Section: Introductionmentioning
confidence: 99%